Building Islamic Awareness in Daily Life: The Role of Teachers in Islamic Religious Education - Juliani; Nazwa Azzahra Siregar; Nadia; Annisa Raudhatul Jannah; Luthfi Az Zahra (Journal of Contemporary Islamic Primary Education, 2024)
This study adopts a qualitative approach with descriptive methods through literature studies to analyze the role of Islamic Religious Education teachers in developing students' character. Islamic Religious Education Teachers not only play a role in providing knowledge, but also as mentors who help students develop the morals, ethics and religious values needed to form individuals with noble character. Instilling religious awareness in everyday life, such as getting used to worship, is the focus in forming students' character. Teachers play an important role in instilling religious principles to form moral behavior in accordance with Islamic teachings, through habits such as congregational prayer, dhikr, and memorizing murojaah. This character development also aims to create individuals who are independent, responsible and contribute to society, as well as building a civilization that is in accordance with Islamic values. Islamic Religious Education, as regulated in Government Regulation of the Republic of Indonesia Number 55 of 2007, aims to achieve physical and spiritual balance, form a Muslim personality with morals, and guide students towards happiness in this world and the hereafter.